Протоболгарские погребения Подонья и Придонечья Уllll-Х вв.: Проблема поливариантности обряда и этноисторической интерпретации - Аксенов, В.С.; Тортика, А.А. (Степи Европы в эпоху средневековья, 2001)
The paper bears on historical and archaeological interpretation of polyvariant funeral rites among the Protobulgarians, who inhabited the area between the Don and the Seversky Donets rivers. The analysis of the data obtained from the Protobulgarian burial grounds dated back from the VIIIth to the Xth cc. A.D., and the interments containing horse remains in particular, give evidence of the heterogeneous ethnic structure of the tribal and territorial communities, that had left the monuments under discussion. Each community had its own formation history, it determining the proportion of specific ethnic features of their funeral rite. The authors suggest classification of those features and their comparative characteristics. They also propose hypotheses for explaining the phenomenon of polyvariant funeral rites.